Mental health literacy among residents in Shanghai - Wang, Jingyi (Editorial Department of the Shanghai Archives of Psychiatry, 2013)
BACKGROUND: The recent adoption of China's new national mental health law provides a good opportunity to obtain baseline information about community mental health literacy in the country. AIM: Assess knowledge and attitudes about mental disorders among residents in Shanghai. METHODS: A total of 1953 residents aged 15 or above selected from all 19 districts in Shanghai completed two self-report questionnaires – the Mental Health Knowledge Questionnaire (MHKQ) and the Case Assessment Questionnaire (CAQ). MHKQ total scores range from 0 to 20 (higher scores indicate better mental health literacy). The CAQ presents respondents with five case vignettes and possesses nine questions after each vignette measuring respondents' knowledge and attitudes towards these mental illnesses. RESULTS: Correct response rates for the 20 MHKQ items ranged from 26 to 98%, with a mean rate of 72%. The internal consistency (alpha) of the 20 items on the MHKQ was 0.69, but this decreased to 0.59 after removing four items about mental health promotion. A 5-factor model for the 20 items in the MHKQ was identified using exploratory factor analysis on one-half of the surveys, but the model was only partially validated in the confirmatory factor analysis using the second half of the surveys. On the CAQ, rates of correct recognition of mania, depression, schizophrenia with positive symptoms, schizophrenia with negative symptoms and anxiety were 42%, 35%, 30%, 19% and 21%, respectively. Work stress (37.3%), problems with thinking (30.0%) and negative life events (24.4%) were reported to be the three main causes of mental disorders. Seeing a counselor (34.2%) or a psychiatrist (33.3%) were the two most common suggestions for help-seeking. Higher education and younger age were related with better mental health literacy and higher rates of recognition of common mental disorders. CONCLUSIONS: Mental health literacy in Shanghai appears to be increasing, but the reliability and validity of the instruments used to assess mental health literacy (MHKQ and CAQ) have not been adequately assessed so this result must be considered preliminary. Further work, preferably including both qualitative and quantitative components, is needed to revise these instruments before they can be used to assess the effectiveness of mental health promotion campaigns.